Edukasi Pencegahan Perbuatan LGBT Di Lingkungan Sekolah Agama Berasrama Penuh Maahad Ahmadi Negeri Sembilan (SABP MANS) Malaysia: Edukasi Pencegahan Perbuatan LGBT Di Lingkungan Sekolah Agama Berasrama Penuh Maahad Ahmadi Negeri Sembilan (SABP MANS) Malaysia - Taufik Siregar; Retna Astuti Kuswardani; Dewi Siregar, Fitri Yanni; Ida Sari Siregar; Erwin Hasibuan (Pelita Masyarakat, 2025)
LGBT behavior is a form of sexual deviance. Deviant sexual behavior in adolescents is caused by the way teenagers socialize freely and tends to be limitless, caused by the sexual urges that are developing in adolescents. Education about faith so far seems to have not been able to produce a generation that is steadfast, strong, and has high dedication to their religion. The method of implementing direct counseling is the method used in this community service activity. Counseling is carried out by visiting the location and providing materials related to Education on Preventing LGBT Acts in the Full Boarding Religious School Environment of Maahad Ahmadi Negeri Sembilan (SABP MANS) Malaysia. The results of the service show that the emergence of the LGBT phenomenon in schools is caused by various factors, such as lack of affection from parents, watching on social media, bad company, and having been a victim. Among the roles that the school can play include, first, providing socialization about LGBT. However, preventing LGBT students will not produce maximum results if it only relies on the school. Support and supervision from parents and the government are also very much needed, such as parental supervision of student viewing.